Climate Change and Global Crop Productivity - Reddy, K. R.; Hodges, H. F.; Ebooks Corporation (Wallingford : CABI, 2000)
Written by international experts, this book is a comprehensive examination of the potential effects climate change, particularly greenhouses gases, will have on agrosystems. It also reviews the effects such systems have on climate change itself.
Contenido: 11 Crop Ecosystem Responses to Climatic Change: Tree Crops12 Crop Ecosystem Responses to Climatic Change: Productive Grasslands; 13 Crop Ecosystem Responses to Climatic Change: Rangelands; 14 Crop Ecosystem Responses to Climatic Change: Crassulacean Acid Metabolism Crops; 15 Crop Ecosystem Responses to Climatic Change: Crop/Weed Interactions; 16 Crop
Libro electronico adquirido a perpetuidad con la editorial CABI
Keywords: CAMBIOS CLIMATICOS